Depression, anxiety, fear of progression, and emotional arousal in couples after left ventricular assist device implantation - Nina Waldenburger; Marnie Steinecke; Luisa Peters; Finja Jünemann; Christoph Bara; Tanja Zimmermann (ESC Heart Failure, 2020)
Abstract Aims Left ventricular assist device (LVAD) is a common treatment option for patients with heart failure waiting for a donor heart. Living with an LVAD is associated with many burdens and worries. Patients often depend on the support of their relatives, usually their spouses. This can also put a strain on the spouses and be associated with psychological stress for both. In couples, communication proves to be an important form of emotional support. Besides verbal aspects of communication, the extent of emotional arousal (f0) that is vocally encoded plays an essential role as a non‐verbal aspect of communication. This study aims to investigate the psychological impact of LVAD on couples in investigating to what extent depression, anxiety, and fear of progression (FoP) differ between patients and partners, the intrapersonal and interpersonal associations of anxiety, depression, and FoP, and differences in emotional arousal. Methods and results In this cross‐sectional study, male LVAD patients and their female partners (N = 21 couples) responded to self‐report questionnaires on depression, anxiety, and FoP. Emotional arousal (f0) was evaluated during social support interactions between both spouses. Female partners experienced more anxiety than male patients (P = 0.016). No differences occurred in depression (P = 0.967) and FoP (P = 0.084). Regarding intrapersonal associations, for patients, correlations appeared between anxiety and depression (r = 0.859, P = 0.000), anxiety and FoP (r = 0.730, P = 0.000), and depression and FoP (r = 0.608, P = 0.004). For caregivers, correlations appeared between anxiety and depression (r = 0.906, P = 0.000), anxiety and FoP (r = 0.665, P = 0.001), and depression and FoP (r = 0.734, P = 0.000). Regarding interpersonal associations, correlations were found between patient's anxiety and caregiver's anxiety (r = 0.461, P = 0.041), caregiver's depression (r = 0.510, P = 0.018), and caregiver's FoP (r = 0.524, P = 0.015). Non‐significant correlations were found for caregiver's anxiety and patient's FoP (r = 0.404, P = 0.078) and patient's depression (r = 0.286, P = 0.236). Patient's depression was associated with caregiver's FoP (r = 0.526, P = 0.017), but not with caregiver's depression (r = 0.337, P = 0.146). No significant correlations were found between caregiver's depression and patient's FoP (r = 0.386, P = 0.084) and patient's depression (r = 0.337, P = 0.146). Patient's and caregiver's FoP showed significant associations (r = 0.482, P = 0.027). Patient's and partner's f0 were interrelated. Patient's f0 was positively related with his own and his partner's psychological distress. Partner's f0 showed associations to her own depression and FoP. Conclusions Findings indicate that women of LVAD patients are burdened similarly or even to a greater extent than men themselves. Women's psychological distress has an impact on patients' psychological distress and vice versa. Early interventions for both patient and partner represent a necessary intervention target.